Impact of Covid-19 on informal employment: A case study of women domestic workers in Khyber Pakhtunkhwa, Pakistan. - Adnan Ahmad Dogar; Ikram Shah; Tahir Mahmood; Noor Elahi; Arif Alam; Urooj Gul Jadoon (PLoS ONE, 2022)
COVID-19 indiscriminately impacted all the segments of the global society. Due to the unstructured job market, women in the informal sector were at high risk to experience the adverse effects of the pandemic. This paper aims to explore the impact of COVID-19 on women domestic workers and their families. Semi structured interviews conducted with fifty-four women domestic workers in three districts of Khyber Pakhtunkhwa, Pakistan were analyzed in five themes: disruption caused by lockdown, loss of livelihood, economic hardships, social support mechanism, and challenges faced during the pandemic. The study underlines that the pandemic left severe impacts on access to basic services, employment, food security at household level and pattern of expenditures. The plummeting economic activities led to sudden drops in earnings that forced families to sell their assets and incur debts. Respondents lamented over the social support system and considered it a necessary but not sufficient condition for uplifting the lives of the poor. Strains in marital relationships led to stress, anxiety and domestic violence among families. The utmost concern was the restoration of economic activities and urgent policy interventions to strengthen social safety measures for the vulnerable segments of society.